Efforts to Improve Critical Thinking Skills Through a Whole Language Approach in Elementary Schools - Sri Wulandari; Evita Elyanti (Journal of General Education Science, 2024)
This research was conducted with the aim of describing: (1) learning in material conveying fairy tale content developed using a whole language approach for elementary school (SD) students (2) changes in elementary school students' attitudes after receiving material conveying fairy tale content using a whole language approach, and (3) elementary school students' learning achievement after receiving material to convey the contents of fairy tales using a whole language approach. This research includes case study research. The subjects of this research were second grade elementary school students. The data collection techniques used were observation, interviews and tests. Test the validity of the data in this research by triangulating data sources, triangulating methods, and informant reviews. The results of the research show (1) the application of the whole language approach in conveying fairy tale content is carried out through the enjoyment stage, appreciation stage, and understanding stage, (2) the attitude changes that occur include (a) increasing critical thinking skills, (b) understanding the correlation between images in words, c) activeness when watching videos and discussing, (d) embedding cooperation and respect between students, and (e) increasing speaking skills, (3) all students experienced an increase in learning achievement with a score of 77-95 through three domains, namely cognitive domain, affective domain, and psychomotor domain.